New Insurance Financial instrument on market: takaful – Islamic insurance (Вестник КазНУ. Серия Экономическая, 2016)
Unfortunately, the traditional form of commercial insurance does not meet all the requirements and needs of consumers in the Republic of Kazakhstan.Insurance, which is an integral part of the financial relations of Islamic finance is updated.Islamic insurance is available in two basic models: Mudaraba and Wakala.Initially, the Islamic finance (Islamic bank-ing) raised the issue of insurance, but in the end was criticized by Islamic jurists.Will this type of insurance in our country.What are the features and benefits of the traditional Islamic insurance.